Study of the drying kinetics of black mulberry (Morus nigra L.) leaves - PINHEIRO, Gleyce Kelle Ilidio; OLIVEIRA, Daniel Emanuel Cabral de; RESENDE, Osvaldo; ROMANI, Viviane Patrícia; GOMES, Francileni Pompeu (Food Science and Technology, 2024)
Black mulberry leaves have been used to promote health and prevent diseases due to their biological properties. Drying leaves allows greater stability during storage and marketing. However, studying this operation is important to ensure that the properties are maintained. Therefore, the objective of this study was to use mathematical modeling to define the model that best fits to the experimental data of the drying kinetics at temperatures of 40, 50, 60, and 70°C. Liquid diffusion, leaf surface area, the relationship between temperature increase and diffusion coefficient, and energy activation were also determined. Among the mathematical models studied, the Page model was the one that best described the drying process of black mulberry leaves. As for the diffusion coefficient, the values increase as the drying temperature increases. The activation energy was 65.418 kJ mol-1, and it was observed that the lower the activation energy, the greater the water diffusivity in the product. The drying kinetics data of black mulberry leaves allowed a better understanding of this operation in a matrix with wide application potential. Drying black mulberry leaves at different temperatures altered their color. Considering the evaluations, temperatures of 40 and 50°C are the most indicated for drying black mulberry leaves.